Peningkatan Bahasa Pada Anak Melalui Kegiatan Story Telling ( PTK Di PAUD Oryza Sativa Kabupaten Kepahiang) - Turrahim, Massila; Asnawati, Asnawati; Haryono, Mimpira (Early Childhood Research and Practice, 2025)
The purpose of this study was to determine the improvement of language in children by using story telling activities at PAUD Oryza Sativa, Kepahiang Regency. This study is a Classroom Action Research (CAR) or also called Classroom action research with the procedure used in the form of a cycle. The subjects of this study were children in group A at PAUD Oryza Sativa, Kepahiang Regency, totaling 20 children. The study was conducted in three cycles. Data analysis was carried out in qualitative and quantitative descriptions with the emphasis being used to determine the improvement of the process expressed in a predicate, while quantitative analysis was used to determine the improvement of results using percentages. The results of improving language skills in children by using story telling activities at PAUD Oryza Sativa, Kepahiang Regency in cycle I with a percentage of 32.81%, in cycle II with a percentage of 56.25%, and cycle III with a percentage of 82.5%. The conclusion of the study is that using story telling activities can improve language skills in children at PAUD Oryza Sativa, as evidenced by an increase in cycle III with a percentage of achievement of 82.5% with the criteria of developing very well (BSB).